Antioxidant capacity of sangre de grado (Croton palanostigma) on gastric mucosa in experimentation animals - Sandoval, Miguel (2006)
Introduction: Sangre de grado use in gastritis and gastric ulcer treatment is done empirically. In previous investigations we have observed sangre de grado both gastric mucosa healing and protection capacity by stimulating mucous secretion, gastric juice secretion without pH change, and increase in peptic activity; due to its components it may have also antioxidant capacity, thus strengthening its citoprotector activity. Objective: To determine sangre de grado(Croton palanostigma) antioxidant capacity on gastric mucosa in experimentation animals by using TBARS test. Design: Prospective, analytic-experimental and longitudinal study. Setting: Biochemistry and Nutrition Research Center, Faculty of Medicine, UNMSM. Biologic material: Forty male albino rats between 200 and 250 g. Interventions: Following 24 hours solid food fasting, the rats received by orogastric cannulation and in unique dose the following: Basal group: glucose 37,5 kcal/kg. Alcohol supplied group: alcohol 37,7 kcal/kg in glucose solution. Control group: alcohol 37,7 kcal/kg with piroxicam 10 mg/kg in glucose solution. Experimental group: alcohol 37,7 kcal/kg plus sangre de grado 0,8 mL/kg in glucose solution. All animals received water ad libitum. Six hours afterwards, abdominal surgery was practiced under vaporized ether anesthesia, the stomachs were extracted and a representative portion of approximately 0,5 g of their glandular portions was obtained. The gastric tissue was homogenized with buffer sodium phosphate 50 mmol/L, at 7,4 pH. Lipoperoxidation was determined by measuring substances reactive to thiobarbituric acid (TBARS), via espectrofotometry at 535 mm, finally expressed by gastric tissue gram. Main outcome measures: Sangre de grado (Croton palanostigma) antioxidant capacity on gastric mucosa in experimental animals. Results: Lipoperoxidation was as follows: basal group 12,11 + 5,24, alcohol supplied group 22,58 + 6,3, control group 14,60 + 5,4, experimental group 17,67 + 3,53. Student t was 2,34, with p<0,025 showing significative difference. Conclusions: In experimental conditions, the orogastric administration of sangre de grado had antioxidants effects on gastric mucosa; lower lipoperoxidation in the alcohol supplied group indicated cytoprotective action.